Genetics and hybrid breeding of Pleurotus pulmonarius: heterosis, heritability and combining ability - Avin, F.A.; Bhassu, S.; Rameeh, V.; Tan, Y.S.; Sabaratnam, V. (Kluwer (now part of Springer), 2016)
Pleurotus pulmonarius has gained popularity as an edible mushroom in many parts of the world due to its numerous advantageous properties. However, there have been very few instances of successful breeding of any of the various species of Pleurotus. The current study attempted to generate improved strains of P. pulmonarius by establishing a systematic scheme using genetics and hybrid breeding. After assessments of the sample collections, three principal parents, and in turn 22 single spore isolates, were nominated for crossing. Of the 231 crosses done, 88 were compatible, and 46 hybrids were able to form basidiocarps in the first cycle of cultivation (CC1). The significant genetic variations among the crosses moved the study in the direction of diallel design, to gain a greater insight into the heritability of the targeted traits and the general and specific combining ability (GCA and SCA) of the parents; and at the same time to estimate their genetic variance components. Mean and heterosis analyses were used to score the obtained hybrids, leading to the selection of four hybrids for CC2, and ultimately three superior hybrids for CC3. The GCA indicated that the Thai strain was the best combiner, while the highest values of SCA were observed in combinations between the Thai and PL27 strains. The genetic variance components and heritability analyses indicated that the bulk of the total genetic variations observed for most traits were associated with genes which were dominant in their effects. The newly generated hybrids were identified by both morphological and molecular fingerprinting (PCR–RFLP). This research involved a successful initial attempt to use a broad range of analyses and the systematic integration of genetics and breeding to assist in generating superior hybrids of P. pulmonarius.